Ocean mixing during Hurricane Ida (2021): the impact of a freshwater barrier layer - Miles, Travis N.; Coakley, Samuel J.; Engdahl, Julia M.; Rudzin, Johna E.; Tsei, Senam; Glenn, Scott M. (Frontiers in Marine Science, 2023)
Tropical cyclones are one of the costliest and deadliest natural disasters globally, and impacts are currently expected to worsen with a changing climate. Hurricane Ida (2021) made landfall as a category 4 storm on the US Gulf coast after intensifying over a Loop Current eddy and a freshwater barrier layer. This freshwater layer extended from the coast to the open ocean waters south of the shelf-break of the northern Gulf of Mexico (GoM). An autonomous underwater glider sampled this ocean feature ahead of Hurricane Ida operated through a partnership between NOAA, Navy, and academic institutions. In this study we evaluate hurricane upper ocean metrics ahead of and during the storm as well as carry out 1-D shear driven mixed layer model simulations to investigate the sensitivity of the upper ocean mixing to a barrier layer during Ida’s intensification period. In our simulations we find that the freshwater barrier layer inhibited cooling by as much as 57% and resulted in enhanced enthalpy flux to the atmosphere by as much as 11% and an increase in dynamic potential intensity (DPI) of 5 m s-1 (~9.72 knots) in the 16 hours leading up to landfall. This highlights the utility of new ocean observing systems in identifying localized ocean features that may impact storm intensity ahead of landfall. It also emphasizes the northern Gulf of Mexico and the associated Mississippi River plume as a region and feature where the details of upper ocean metrics need to be carefully considered ahead of landfalling storms.